Learning through multi-touch interfaces in museum exhibits: An empirical investigation - Zaharias, Panagiotis; Michael-Grigoriou, Despina; Chrysanthou, Yiorgos L. (My University, 2013)
Interactive technologies are employed in museums to enhance the visitors' experience and help them learn in more authentic ways. Great amounts of time and money and many man-hours of hard work have been spent. But do such systems indeed achieve their goals? Do they contribute to a greater user experience (UX) and learning effectiveness? In this paper we describe the use of the "Walls of Nicosia" a 3D multi-touch table installed at the Leventis Municipal Museum in Nicosia, Cyprus. Two groups of students actively participated in this empirical study (they attended the 5th year class at elementary school, all aged from 10 to 11 years old): a) The traditional group (control group) where students took a guided tour throughout the museum and learned about the walls of Nicosia through printed maps exhibited at the museum and b) the virtual group where students interacted with the multi-touch application. The main aim of the study was to assess the learning performance and user experience between the two groups. Results showed no statistically significant differences in the learning performance but the virtual group reported user experience at significantly higher levels. The main findings are discussed and ideas for future research are presented.
Keywords: Elementary education; Evaluation methodologies; Interactive learning environments; Multimedia/hypermedia systems; Virtual reality